APEC and the new regionalism : GATT compliance and the prescriptions for the WTO. - FAYE, Andrew A. (1996)
Discusses the development of APEC into an outward-looking regional bloc, focusing on concerted unilateralism in trade liberalization, trade facilitation, and business promotion. Sees APEC as representative of a new form of regional grouping, and advises that if properly exploited, APEC, as well as future regional institutions that may form in its image, may further the process of achieving multilateral free trade.